Asia Pacific regional convention 15th-16th August 2004 Bangkok, Thailand. (Thomas Telford, 2004)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings Asia-Pacific regional convention held in Bangkok on 15-16 August 2004.